Efficacy of fungal endophytes of tea ecosystem for the management of blister blight - Raj, Ritika; Dutta,Pranab (Umiam : CPGSAS, CAU(Imphal), 2024)
India, a global tea titan contributing a quarter (23%) of the world's tea harvest, with Assam alone supplying more than half (52%), faces a formidable threat in blister blight, a devastating disease caused by the insidious fungus Exobasidium vexans. This scourge inflicts a staggering 40% loss in tea production. To shield this economic mainstay, a comprehensive investigation was undertaken in India's northeastern regions to devise an integrated strategy to combat this affliction. This study delved into the potential of endophytic fungi, microbial inhabitants of plant tissues, as a biological shield. In the present study 46 fungal endophytes were isolated from the stem, leaf and roots of tea of 9 gardens of 3 north eastern states of India and were characterized. During the study, it was found that roots harbored Beauveria bassiana, Verticillium lecanii, two species of Trichoderma and diversed Fusarium spp, the stem was a domain for Metarhizium robertsii, Colletotrichum spp, and three species of Trichoderma. Out of entire isolates, 30 isolates with vigorous growth were meticulously characterized and tested for their in-vitro efficacy against the E. vexans causing blister blight of tea. Results showed, Trichoderma harzianum (A2S3) as the most effective antagonist, exhibiting 74.4% mycelial inhibition against E. vexans. Its mode of action was found to be involved a predatory strategy of coiling, penetrating, lysis of the pathogen's cell wall. Beyond its antifungal potential, this beneficial microbe showcased plant growth-promoting attributes, like ammonia production, siderophore production (71.1%), phosphate solubilization (83%), and zinc solubilization (17.1%).Field trial conducted in two tea gardens of Dhubri District of Assam showed that 3 foliar spray of T. harzianum (A2S3) liquid bioformulation @10 ml/l, installation of yellow sticky trap (2 no./300 m2), removal of odd and damaged plant parts, regular weeding and irrigation showed effective in mitigating other insidious plant diseases such as Fusarium die back (15.3% and 0.7%) and grey blight caused by Pestlioptiopsis thea upto 6.5%, 20.4% respectively in Maa Phulaswari MTG and Saslapara NTG, Dhubri, Assam. The treatment also found to reduce the infections of RSM (10.3% and 17.1%) and TMB upto 4.3% and 8.2% in Maa Phulaswari MTG and Saslapara NTG, Dhubri, Assam respectively. Concurrently, it fostered a healthier ecosystem by improving plant growth parameters such as inter-node length, specific leaf weight, per cent moisture content besides soil physiochemical properties such as soil pH, soil EC by enriching soil organic carbon (1.6% and 1.2%) and stimulating microbial diversity (fungal- 76 and 106 cfu/ml, bacteria- 306 and 296 cfu/ml). The tea plant itself responded positively, with elevated levels of protective compounds phenol (208.54 ppm) and flavonoid (346.16 ppm) content in Maa Phulaswari mini tea garden and higher TSS (158.81 ppm) and TSP (115.73 ppm) in Saslapara new tea garden, Dhubri, Assam. Further research is warranted to evaluate the in- vivo efficacy and develop suitable formulations for field applications. This eco-friendly approach could offer a sustainable solution for tea disease management, reducing reliance on chemical fungicides.
Includes bibliographical references.
Keywords: Tea -- Blister blight disease; Disease -- Management -- Biocontrol